Effectiveness of an Evidence-Based Quality Improvement Approach to Cultural Competence Training: The Veterans Affairs' "Caring for Women Veterans" Program. Issue 2 (2016) - Fox, Annie B.; Hamilton, Alison B.; Frayne, Susan M.; Wiltsey-Stirman, Shannon; Bean-Mayberry, Bevanne; Carney, Diane; Di Leone, Brooke A. L.; Gierisch, Jennifer M.; Goldstein, Karen M.; Romodan, Yasmin; Sadler, Anne G.; Yano, Elizabeth M.; et al.
Abstract : Introduction: Although providing culturally sensitive health care is vitally important, there is little consensus regarding the most effective strategy for implementing cultural competence trainings in the health care setting. Evidence-based quality improvement (EBQI), which involves adapting evidence-based practices to meet local needs, may improve uptake and effectiveness of a variety of health care innovations. Yet, to our knowledge, EBQI has not yet been applied to cultural competence training. To evaluate whether EBQI could enhance the impact of an evidence-based training intended to improve veterans affairs health care staff gender sensitivity and knowledge (Caring for Women Veterans; CWV), we compared the reach and effectiveness of EBQI delivery versus standard web-based implementation strategies of CWV and assessed barriers and facilitators to EBQI implementation. Methods: Workgroups at four diverse veterans affairs health care sites were randomized to either an EBQI or standard web-based implementation condition (SI). All EBQI sites selected a group-based implementation strategy. Employees ( N = 84) completed pretraining and posttraining assessments of gender sensitivity and knowledge, and focus groups/interviews were conducted with leadership and staff before and after implementation. Results: Reach of CWV was greater in the EBQI condition versus the SI condition. Whereas both gender sensitivity and knowledge improved in the EBQI condition, only gender sensitivity improved in the SI condition. Qualitative analyses revealed that the EBQI approach was well received, although a number of barriers were identified. Discussion: Findings suggest that EBQI can enhance the uptake and effectiveness of employee trainings. However, the decision to pursue EBQI must be informed by a consideration of available resources. Abstract : Supplemental Digital Content is Available in the Text.